2011
DOI: 10.1308/003588411x563402
|View full text |Cite
|
Sign up to set email alerts
|

Acalculous gallbladder disease: the outcomes of treatment by laparoscopic cholecystectomy

Abstract: We therefore conclude that laparoscopic surgery for patients with acalculous gallbladder disease is effective in symptom control and allowing patients to return to their normal lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…However, ultrasound is highly accurate for steatosis and is widely used clinically and in population-based studies [ 71 ]. Second, the information on the indications for cholecystectomy was not available; thus, we could not differentiate cholecystectomy unrelated to gallstones [ 35 , 36 ]. However, the majority of gallstones are not associated with symptoms [ 72 ]; thus, incidental asymptomatic gallstones as a separate outcome in our study could lead to a better understanding of the development of gallstones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ultrasound is highly accurate for steatosis and is widely used clinically and in population-based studies [ 71 ]. Second, the information on the indications for cholecystectomy was not available; thus, we could not differentiate cholecystectomy unrelated to gallstones [ 35 , 36 ]. However, the majority of gallstones are not associated with symptoms [ 72 ]; thus, incidental asymptomatic gallstones as a separate outcome in our study could lead to a better understanding of the development of gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…A cholecystectomy can be performed due to acalculous gallbladder diseases such as gallbladder polyps, tumors, acalculous cholecystitis, and biliary dyskinesia, which collectively represent between 5% and 30% of laparoscopic cholecystectomies [ 35 , 36 ]. Because the indications for the cholecystectomies were not available, we used ultrasound-documented gallstones as the primary endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Her abdominal pain was worsening, she did not tolerate pain medications and she had high EBV viral load which usually correlates with disease severity [ 11 ]. Conservative management was advised initially but she opted for surgery and had laparoscopic cholecystectomy [ 12 , 13 ]. She received a single dose of intravenous Cefazolin preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that surgery was effective in controlling symptoms and allowing patients to return to normal lifestyle. 19 Jones-Monahan et al demonstrated that among 45 symptomatic patients with GBPs and no stones who underwent cholecystectomy, 93% reported relief of symptoms. 20 , 21 The remaining two patients experienced dyspepsia that did not interfere with daily activity.…”
Section: Discussionmentioning
confidence: 99%